On the Oscillation of the Generalized Food-Limited Equations with Delay - Bala M. Abdulhamid; Yusuf Haruna; Bamaina M. Muhammad (Graduate Program of Syiah Kuala University, 2012)
Abstract - The objective of the paper is to find conditions for the oscillation of the food-limited equation. We established conditions for the oscillation of all solutions of the generalized foodlimited equation by transforming the equation to a non-linear delay differential equation and then to a scalar delay differential equation and using the property of the scalar delay differential equation to obtain our result. Similarly we establish conditions for the oscillation of all solutions of the foodlimited equation with several delays by transforming the equation to a scalar differential equation to obtain the oscillatory property.